Establishment of a clinical pharmacist-led multiple myeloma clinic with collaborative prescribing model at the national center for cancer care and research in Qatar - Rola Ghasoub (16555851) (2024)
Background Multiple myeloma (MM) is a chronic and incurable hematologic malignancy that is prevalent among the elderly. Interprofessional patient care showed superiority over physician-only care in multiple settings, including MM. Objective The primary objective of this study was to evaluate the impact of clinical pharmacist (CP)-led clinic and CPs interventions on MM patient care. Practice description Real-world analysis of ambulatory patients with MM showed that CPs were central to the optimization of therapy and adherence to treatment schedules and supportive medications. Practice innovation The CP-led MM Clinic was established with a collaborative prescribing agreement (CPA) in 2022 at the National Center for Cancer Care and Research in Qatar and was the first of its kind in the Middle East and North Africa region. This CPA allowed CPs to issue refills for supportive medications and order required laboratory tests. Evaluation methods Data collected included the number of CP interventions, refills ordered by CPs, documentation of patient education, and medication reconciliations. The data were retrospectively collected and analyzed comparing ambulatory patients with MM treated before (2021) to those treated after the clinic implementation in 2022. Results The study population comprised 22 patients. A higher number of CPs interventions were documented post-clinic than preclinic (343 vs. 76, P = 0.004), with earlier initiation of bisphosphonate post-clinic (25 vs. 206 days, P = 0.008). There were also significant improvements in the introduction of risk appropriate venous thromboembolism prophylaxis (43% vs. 6%, P = 0.001) as well as vitamin D and calcium supplementation (100% vs. 68%, P = 0.02) post-clinic. Twenty-two medication refills for supportive medications and eight prechemotherapy laboratory investigations were ordered by CPs. Conclusion The CP-led clinic provided a timely link to care optimization for ambulatory MM patients. This innovative CPA model implemented in the clinic could potentially be applied to different cancer settings to optimize safe and effective patient care. Other Information Published in: Journal of the American Pharmacists Association License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.japh.2024.102141